Pengaruh Gross Profit Margin (GPM) Dan Debt To Equity Ratio (DER) Terhadap Return On Assets (ROA) Pada Perusahaan Industri Batubara Yang Terdaftar Di BEI Periode 2020-2024 - Fadlillah Ramadhan; Meilanie Tri Pratiwi; Kylla Almira Rahma Fadzillah; Dini Nurhandayani; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to examine the effect of Gross Profit Margin (GPM) and Debt to Equity Ratio (DER) on Return on Assets (ROA) of coal industry companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study applies a quantitative approach with a descriptive research design. The data used are secondary data obtained from annual financial statements and analyzed using panel data regression. Based on the model selection results using the Chow test and Hausman test, the Random Effect Model was selected as the best estimation model. The results show that partially GPM has a positive and significant effect on ROA, while DER has a negative and significant effect on ROA. Simultaneously, GPM and DER have a significant effect on ROA. The R-squared value of 0.653058 indicates that GPM and DER explain 65.31% of the variation in ROA, while the remaining variation is explained by other variables outside the model. This study is expected to provide empirical evidence in analyzing profitability performance in coal industry companies.